A Late Pleistocene archaic human tooth from Gua Dagang (Trader’s Cave), Niah national park, Sarawak (Malaysia) - Darren Curnoe; Mohammed S. Sauffi; Hsiao Mei Goh; Xue-feng Sun; Roshan Peiris (PLoS ONE, 2025)
The rarity of Late Pleistocene hominin remains from Insular Southeast Asia (ISEA) has hampered our ability to understand a crucial episode of human evolutionary history, namely, the global dispersal of Homo sapiens from Africa. Moreover, recent discoveries indicate a surprising level of taxic diversity during this time with at least two species— H. floresiensis and H. luzonensis —endemic to the region when H. sapiens first arrived. A third hominin dubbed the ‘Denisovans’ is shown from DNA evidence to have interbred with the ancestors of contemporary Indigenous populations across ISEA, New Guinea and Australia. Yet, the Denisovans have not been identified from the fossil record of the area despite recent breakthroughs in this regard on mainland East Asia. New excavations by our team at the Trader’s Cave in the Niah National Park (‘Niah Caves’), northern Borneo, have yielded an isolated hominin upper central permanent incisor dated with Optically Stimulated Luminescence dating of sediments to about 52 − 55 thousand years ago. Specimen SMD-TC-AA210 has a massive crown absolutely and relative to its root size, the crown is wide (mesiodistally) and relatively short (labiolingually). Morphologically, it exhibits a very strong degree of labial convexity, pronounced shovelling, and the bulging basal eminence exhibits several upward finger-like projections. Labial enamel wrinking on the enamel-dentine junction is expressed as two large ridges exhibiting numerous spine-like projections, and the lingual extensions on the enamel surface of the basal eminence are expressed as six extensions. This combination of crown size and morphological traits is not normally found in H. sapiens and instead characterises archaic members of Homo such as H. erectus , H. neanderthalensis and Middle Pleistocene hominins sharing a clade with H. heidelbergensis. The Trader’s Cave tooth suggests that an archaic hominin population inhabited northern Borneo just prior to or coincident with the arrival of H. sapiens as documented at the nearby West Mouth of the Niah Great Cave.